PERANCANGAN TURBIN ANGIN SAVONIUS UNTUK SISTEM PENERANGAN DENGAN STRIP LED PADA JEMBATAN (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2022)
Today the availability of energy sources in the future is a global problem that continues to be the concern of all countries in the world. Electrical energy is one of the most basic needs in a country, especially in Indonesia. In addition to the problem of the need for electrical energy, lighting in the bridge area is also still a polemic to this day. Based on the studies that have been carried out, it is necessary to maximize the utilization of renewable energy sources, one of which is wind energy as a supplier of electrical energy by applying the concept of a wind power plant (PLTB). Based on the problems that have been described, a creative and innovative idea was initiated to help lighting on bridges in an effort to reduce the number of traffic accidents with the design title Savonius wind turbines for lighting systems with LED strips on bridges.